Analysis of Agricultural Agribusiness Development: Literature Review of Challenges and Opportunities in the Modern Era - Berlian, Mery (Yayasan Abdurrauf Cendekia Nusantara, 2025)
Agricultural agribusiness is an important sector in the economic development and food security of a country. In the last two decades, agribusiness has undergone significant transformation influenced by technological advances, climate change, and globalization. This article is a literature review that analyzes various scientific literature on the development of agricultural agribusiness, the challenges faced, and the opportunities that can be utilized. This study uses a descriptive qualitative approach with a literature study method from national and international scientific journals. The results of the study indicate that the main challenges of agribusiness today include dependence on imported inputs, low adoption of digital technology, and climate uncertainty. However, there are great opportunities through the development of agritech, product diversification, and strengthening of digital-based supply chains. This study recommends the need for collaboration between the government, private sector, and farmers in encouraging sustainable agribusiness growth.